A Novel Berberine–Glycyrrhizic Acid Complex Formulation Enhanced the Prevention Effect to Doxorubicin-Induced Cardiotoxicity by Pharmacokinetic Modulation of Berberine in Rats - Zhang, Shichang; Zhao, Yiwei; Tan, Liangjun; Wu, Sheng; Zhang, Qing; Zhao, Boxin; Li, Guofeng (Frontiers in Pharmacology, 2022)
Developing a new drug delivery system is one of the useful approaches to overcome the limited use of berberine (BBR) to enhance its absorption and bioavailability. We prepared a novel berberine–glycyrrhizic acid (BBR–GL) complex formulation to increase the plasma concentration and bioavailability of BBR by improving BBR solubility and lowering the absorption barrier. The complex formulation with BBR and GL in the ratio 1:1 was developed through the self-assembly process and evaluated in vitro. Compared with BBR and BBR/GL physical mixture, the BBR–GL complex showed different characteristics by SEM, DSC, FT-IR, and PXRD measurement. In pharmacokinetic evaluation, the BBR–GL complex significantly increased the plasma concentration of BBR and the major metabolite berberrubine (BBB), with the AUC of BBR elevated to 4.43-folds, while the complex was safe as BBR. Furthermore, doxorubicin (DOX) was used to induce cardiotoxicity. Hematological study, histopathological examinations, electrocardiography (ECG), cardiac secretion measurement, and biochemical index analysis proved that the model of doxorubicin-induced cardiotoxicity (DIC) was conducted successfully. With the AUC of BBR increasing in the BBR–GL complex and the absorbed complex itself, the BBR–GL complex enhanced prevention effect to DIC and exhibited a significant prevention effect to attenuate heart damage. Our findings demonstrated that a novel BBR-loaded BBR–GL complex formulation could increase BBR plasma concentration. Improvement of BBR bioavailability by the BBR–GL complex could coordinate with GL to attenuate DIC. Concerning the safety of the drug delivery system at present, the BBR–GL complex could be a potential therapeutic formulation for the prevention of cardiac damage in the clinical application of doxorubicin.